Pulmonary tuberculosis in childhood nephrotic syndrome (A cross sectional study) - Taralan Tambunan; Attila Dewanti; Bambang Madiyono; Nastiti N Rahayoe (Indonesian Pediatric Society, 2001)
Childhood tuberculosis persists as an important global health problem. Tuberculosis is one of the commonestimportant complications in children with nephrotic syndrome. Tuberculosis may interfere with the response to steroid therapyand is still being the commonest morbidity cause in children with nephrotic syndrome. To find out the prevalence, clinicalfeatures, and the impact of tuberculosis in children with nephrotic syndrome, a cross sectional study was conducted on 100nephrotic children consisted of 63 males and 37 females at the Cipto Mangunkusumo Hospital from April 1st to October 30th,1999. Pulmonary tuberculosis was detected on 15 cases ( 95% CI : 8% - 22% ) , consisted of 8 boys and 7 girls. Most of themaged 10 – 16 years old (66,6%) and 86,7% were undernourished. The combination of clinical judgement, chest X-ray andMantoux test were helpful in establishing the diagnosis. The majority of tuberculosis cases (80%) were detected on frequentrelapsers and steroid dependent groups of the nephrotic syndrome. A significant correlation were noted in tuberculosis withundernutrition and unfavorable response to steroid (frequent relapser and steroid dependent cases).